ARCHITECTURAL CHARACTERISTICS STUDY ON COMMUNITY MOSQUES IN PRIANGAN 1900 – 1942 - Istiqomah, Esti; Budi, Bambang Setia (Journal of Islamic Architecture, 2013)
AbstractPriangan was a region with a distinctive historical background and administrative unity. The region consisted of 7 regencies in present West Java Province. There were some old community mosques in the region. The aim of this paper is to formulate architectural characteristics of Priangan old community mosques and their overall development.  The  mosques  are  no  longer  observable  today.  Therefore,  the  study  is  referring  to  old documentations. The oldest available documentations of such mosques were presented in the form of photos from Dutch colonial era, after the ethical policy. Therefore, the study is limited from the year 1900 to 1942. Based on the photos, the mosques were resketched by outlining the intended variables, which are building mass, transitional space, and roof. There were some common architectural characteristics that can be concluded from Priangan  old  community mosques. The  common characters are  single  mass,  surrounding verandah, and two stacked pyramidal roof. On the overall development, the mosques showed the peak of architectural characteristics variations on the photos that were taken in the year 1925.Keywords:  mosque, Priangan, colonial, characteristic, architecture  AbstrakPriangan  merupakan  suatu  wilayah  yang  memiliki kesamaan  latar  historis  dan  pernah  memiliki kesatuan administrasi. Wilayah ini meliputi 7 kabupaten di Provinsi Jawa Barat saat ini. Di wilayah tersebut terdapat masjid-masjid komunitas lama. Makalah ini bertujuan untuk merumuskan karakteristik arsitektural masjid- masjid komunitas lama yang ada di Priangan serta kecenderungan perkembangan keseluruhannya. Masjid- masjid tersebut saat ini sudah tidak dapat diamati lagi di lapangan. Oleh karena itu, studi karakteristik dilakukan melalui sumber dokumentasi bersejarah. Dokumentasi masjid-masjid tersebut mulai muncul pada masa kolonial Belanda setelah politik etis dalam bentuk foto. Oleh karena itu, kurun waktu kajian dibatasi antara tahun 1900 hingga tahun 1942. Dari foto-foto tersebut, masjid kemudian di sketsa ulang untuk memperjelas  variabel-variabel  yang  akan  dianalisis,  yaitu  massa,  ruang,  dan  atap.  Dari  hasil  analisis, didapatkan karakteristik arsitektural masjid komunitas lama di Priangan yang umum, yaitu memiliki massa tunggal, selasar keliling, dan atap tumpang 2 tumpuk. Kemudian dalam foto masjid-masjid yang diambil tahun1925, karakter arsitektural masjid menjadi semakin beragam.  Kata kunci: masjid, Priangan, kolonial, karakteristik, arsitektur